FACTORES QUE DETERMINAN LA MATERNIDAD ADOLESCENTE. CASO: INSTITUTO NACIONAL MATERNO PERINATAL - Solano Dávíla, Olga Lidia (2009)
In the present work we identified the factors that affect in the teenager maternity in patients of the service of set accommodation of the Instituto Nacional Materno Perinatal (INMP) of Lima using of the theory of multiple logistic regression (Hosmer y Lemeshow, 2000; Uriel, 2005). We made a questionnaire and consider questions with respect to the features of the teenager mothers: education level, age of the union, knowledge of sex education and family planning, and so on. Features home: structure of the household, marital status of parents, union of parents, educational level of parents, number of brothers and sisters, and so on. The final data was taken from October the 2007 to March the 2008, with the application of the final instrument to mothers hospitalized in the services of set accommodation of the INMP. (Solano et. Al, 2007). For the calculus of the size of the samplc we used the proposed Freeman (1987); the mother were select at random until completed the size of the sample of two hundred forty two.